Organizational culture and social responsibility in health care: problems of defining and methods of study - Surmach, Marina Y.; Boyko, Svetlana L. (Journal of the Belarusian State University. Sociology, 2019)
The reasons for the dynamics of the social institute of medicine and the current model of health care system as its organization in modern conditions in the Republic of Belarus are analyzed in the article. The concepts of «organizational culture» and «social responsibility» in relation to the health care system are clarified. The methods of study of organizational culture are stated. A tool for assessing of organizational culture according to the OCAI methodology, adapted to the use in the health care system of Belarus, which allows to diagnose organizational culture in organizations (institutions) of health care, and suitable for use in comparative analysis with the data obtained by measurements through the original version of OCAI in other countries, is proposed.